Trim21 deficiency alleviates osteoporosis by inhibiting osteoclast differentiation through regulating Txnip - Ya-Chen Peng; Yong-Sheng Ye; Qin-Xiao Hu; Zhi-Quan Hao; Zhen-Yan Li; Luo-Yong Jiang; Hao-Ran Peng; Ri-Xu Liu; Zhen-Gang Zha; Huan-Tian Zhang (Arthritis Research & Therapy)
Abstract Objective The tripartite motif containing 21 (Trim21), an E3 ubiquitin ligase, plays a crucial role in the progression of various skeletal diseases, particularly in osteoporosis. In our previous study, Trim21 deficiency was shown to exert dual effects by suppressing bone resorption and enhancing osteogenesis. However, the specific mechanism by which Trim21 inhibits osteoclast (OC) differentiation remains unclear. In this study, we utilized a myeloid cell–specific conditional knockout model of Trim21 to investigate the underlying regulatory mechanisms. Methods OC-specific Trim21 knockout mice were generated and subjected to ovariectomy (OVX) to establish a model of postmenopausal osteoporosis. Bone mass and OC activity were then evaluated using micro-computed tomography (micro-CT) and tartrate-resistant acid phosphatase (TRAP) staining. Bone marrow-derived macrophages (BMMs) were induced to differentiate into OCs, and gene expression levels were detected by qRT-PCR. Additionally, proteomic analysis was performed to identify downstream regulatory proteins influenced by Trim21. Results OC-specific Trim21 deletion alleviated OVX-induced bone loss by inhibiting bone resorption and preserving bone mass. Myeloid-specific Trim21 deletion impaired OC differentiation and suppressed the expression of key OC markers. Thioredoxin-interacting protein (Txnip), was identified as a downstream effector regulated by Trim21. Conclusion Trim21 deletion attenuates osteoporosis-induced bone loss, likely by suppressing osteoclast differentiation through modulation of Txnip, thereby presenting a potential novel therapeutic target for osteoporosis treatment.